2014
DOI: 10.17221/7290-cjas
|View full text |Cite
|
Sign up to set email alerts
|

The effect of non-phytate phosphorus and phytase levels on performance, egg and tibia quality, and pH of the digestive tract in hens fed higher-calcium-content diet

Abstract: THe effect of three levels of non-phytate phosphorus (NPP) (3.0, 2.1, and 1.7 g/kg) and two levels of 3-phytase (F) (0 and 150 phytase units (FTU)/kg) together with a high dietary calcium concentration (approximately 41.0 g/kg) on the performance characteristics, egg quality, pH of the digestive tract, and tibia bone quality of ISA Brown hens housed in enriched cages was evaluated. THe diets with 3.0 g/kg of NPP with and without F and 2.1 g/kg of NPP with 150 FTU of F significantly increased egg production (P … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
5
6
0
Order By: Relevance
“…When the Ca : NPP ratio was narrow, such as in Experiment 1 and in the study by Kim et al (2013), the dietary Mg did not influence the laying intensity, but it increased the eggshell strength. A wide Ca : NPP ratio of 19.5 : 1 and 24 : 1 without Mg supplementation significantly reduced laying intensity in the experiment of Englmaierova et al (2014). A similar relationship was seen in Experiment 2.…”
Section: Discussionsupporting
confidence: 75%
“…When the Ca : NPP ratio was narrow, such as in Experiment 1 and in the study by Kim et al (2013), the dietary Mg did not influence the laying intensity, but it increased the eggshell strength. A wide Ca : NPP ratio of 19.5 : 1 and 24 : 1 without Mg supplementation significantly reduced laying intensity in the experiment of Englmaierova et al (2014). A similar relationship was seen in Experiment 2.…”
Section: Discussionsupporting
confidence: 75%
“…The Scientific Panel on additives and products or substances used in animal feed (FEEDAP Panel), which belongs to the EFSA, concluded that the additive has the potential to be effective in laying hens at a dose of 150 FTU/kg feed. This conclusion was confirmed by Englmaierova et al (2014), who reported that using dietary contents 2.1 g/kg NPP and 41 g/kg Ca with the addition of 150 FTU/ kg 3-phytase Natuphos ® resulted in higher egg production and higher Ca and P concentrations in egg shells compared to the positive control (3 g/kg NPP). Olukosi et al (2013) determined that a high dose of Ph in the diet releases more Ca from phytate and that this greater release is reflected in a higher concentration of Ca in bones.…”
Section: Discussionsupporting
confidence: 53%
“…Based on previous findings that high doses of NPP had a negative effect on hen performance (Skrivan et al 2010;Englmaierova et al 2012Englmaierova et al , 2014a, low levels of NPP were chosen for this study. An increase in the NPP level from 1.8 to 2.1 g/kg significantly decreased egg production, egg weight, and egg mass production and significantly increased the feed intake per hen, the feed intake per egg, and the feed conversion ratio.…”
Section: Discussionmentioning
confidence: 99%